Drone-based observations of scarring patterns in humpback whales (Megaptera novaeangliae) in the New York Bight provide insight into foraging behavior and anthropogenic threats - Siobhan E. Keeling; Chelsi Napoli; Joshua Meza-Fidalgo; Julia S. Stepanuk; Nathan Hirtle; Zachary Hoffman; Lesley H. Thorne (PLoS ONE, 2025)
Large whales face a range of threats, including vessel strikes and entanglement in fishing gear. Elevated humpback whale mortality, predominantly in juveniles, has occurred in the Northeast US since 2016. The New York Bight, a region with dense shipping and fishing vessel traffic, has become a hotspot for these strandings. Scarring patterns can provide information on anthropogenic threats, as well as predation and behavior. We used drone imagery to examine scarring reflective of entanglements, vessel strikes, killer whale interactions and bottom feeding in both juvenile and adult humpback whales in the New York Bight. The vast majority of both adult (87.1%) and juvenile (86.8%) humpbacks showed entanglement scars, indicating that humpbacks frequently interact with fishing gear across age classes. Vessel strike scars were observed more frequently in juvenile whales (14.2%) than in adults (2.2%), in contrast to prior observations north of our study area in the Gulf of Maine, though the difference was of borderline significance (mean p-value 0.051, Fisher’s Exact tests on 1000 bootstrapped populations incorporating uncertainty in length measurements). These results support previous suggestions that juvenile humpbacks in the New York Bight may be particularly vulnerable to vessel strike due to inshore and surface feeding, and suggest that vessel strike scars may be obtained locally. Killer whales are thought to primarily target young animals, and killer whale scars were observed more often in juveniles (11.6%) than adults (4.4%), though this difference was not significant (mean p-value 0.26). Jaw scuffing indicative of bottom feeding was observed more frequently in adults (68.9%) than in juveniles (27.4%; mean p-value 3.47 x 10−5), suggesting that this behavior is acquired as whales mature. Our findings underscore differences in behavior between adult and juvenile humpback whales and highlight the exposure of humpback whales to anthropogenic threats in heavily urbanized coastal regions.